(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
The bronchial system is a vital component of the human respiratory tract, responsible for the conduction and regulation of airflow between the trachea and the lungs. This article provides an anatomical and functional analysis of the bronchial tree, emphasizing its structural organization, branching patterns, and physiological roles. Special attention is given to the mechanisms of airflow regulation, mucociliary clearance, and the protective functions of the bronchial epithelium. The study also examines the relationship between bronchial structure and respiratory efficiency, as well as its relevance to common pulmonary disorders. Understanding the anatomy and function of the bronchial system is essential for improving diagnostic and therapeutic approaches in respiratory medicine.